Multiblock segmented polyurethanes and polyurethane-ureas based on poly(ethylene oxide)/poly(propylene oxide)/poly(ethylene oxide) macrodiols. Synthesis and characterization - Filip, D.; Macocinschi, D.; Ioanid, E.; Vlad, S. (Polimery, 2010)
The amphiphilic behavior of poly(ethylene oxide)/poly(propylene oxide)/poly(ethylene oxide) block copolymers has been broadened by introducing new urethane-urea as well as poly(ethylene glycol) co-segments in polyurethane (PUR) and polyurethane-ureas (PURU) materials. Supermolecular organization and self-assembly was confirmed by electron microscopy transmission observations. The driving force for self-assembling is represented by the amphiphilic nature of these materials, the interactional segment length and stabilization through hydrogen bonding. FT-IR spectroscopy was used to investigate the hydrogen bonding related to phase segregation. Phase transitions and phase segregation was evidenced by DSC analyses. The relationship between structure and thermal stability was investigated by thermogravimetric analysis.